Drug utilization study on antidiabetic medications at SIMS-Shimoga a tertiary care hospital - Vedavathi, H.; Revankar, Shreenivas P. (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Diabetes mellitus (DM) refers to a group of common metabolic disorders that share the phenotype of hyperglycemia. DM is a leading cause of blindness, end stage renal disease, and nontraumatic lower extremity amputations. The objective of the study was to evaluate the drug utilization pattern of antidiabetic medications at a tertiary care hospital. Methods: Demographic details of the patient were noted. Evaluation of the written prescription was carried out according to the requirements in case record form followed by computerization of data and analysis. Results: DM was almost equal in male (51%) and females (49%), the risk of DM was high after 40 years of age. Out of all the case records and prescriptions reviewed it was found that 23% had Type 1 DM, and 77% had Type 2 DM. In 46.35% cases, there was a family history of DM while in 47.44% cases it was absent, 6% were unaware. The average number of drugs per prescription was 3.26±0.24 and antidiabetic drugs at 1.72±0.28. Insulin alone was prescribed in 25.54% cases. Single antidiabetic agents as lone drugs were seen in 39.05%; combined oral antidiabetic drugs accounted for 25.54% cases. The combination of insulin and oral antidiabetic agents were prescribed in 9.85% cases. Conclusion: Metformin was the oral hypoglycemic agents, which was the most frequent prescribed as was insulin and its analogs. These drugs being essential in the treatment of diabetic patients should be made available to patients all the time.